Modeling The Human Development Index in Islamic Economic Perspective: Empirical Evidence from Jambi Province - Elyanti Rosmanidar; Titin Agustin Nengsih (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
Abstract Islam doesn’t teach us to leave us in a weak state in terms of economics, religion, and defence. By carrying out development, a country can improve the welfare of its people, one of which is in the economic fields where economic growth will be an indicator. The purpose of this research is to analyse the influence of poverty, economic growth, unemployment rates, and government expenditure on the human development index in Jambi province. This study uses a quantitative approach using Panel Regression statistical analysis to see the effect of poverty on economic growth, unemployment rates, and government spending on the human development index.Keywords: Human Development Index,Poverty, Government Expenditure, Economic Growth  Abstrak Islam mengajarkan untuk tidak meninggalkan anak cucu kita dalam keadaan yang lemah dalam hal perekonomian, agama dan pertahanan.  Dengan melakukan pembangunan, suatu negara bisa meningkatkan kesejahteraan rakyatnya, salah satunya di bidang ekonomi yang dimana pertumbuhan ekonomi akan menjadi indikatornya. Tujuan dalam penelitian ini adalah untuk menganalisa adanya pengaruh kemiskinan, pertumbuhan ekonomi, tingkat pengangguran, dan pengeluaran pemerintah terhadap Indeks Pembangunan Manusia di Provinsi Jambi. Penelitian ini ini menggunakan pendekatan kuantitatif menggunakan metode uji asumsi klasik dan  analisis statistik regresi berganda untuk melihat pengaruh kemiskinan, pertumbuhan ekonomi, tingkat pengangguran, dan pengeluaran pemerintah terhadap Indeks Pembangunan Manusia.Kata kunci: IPM, Kemiskinan, Pengeluaran Pemerintah, Pertumbuhan Ekonomi